Normative Spiritualization of Parents in The Dynamics of Children's Intellectual Intelligence - Zuhri Fahruddin (An-Nisa' Journal of Gender Studies, 2022)
The enthusiasm to hone children's intellectual intelligence abilities today is minimal as time goes by; this is due to environmental facilities, and there is no interest in knowledge, and most parents do not know that the knowledge gained by children also depends on the seriousness of parents physically and spiritually, with This researcher intends that parents are not only more concerned with physical sincerity, but also spiritual sincerity, just like 15th-century parents who gave birth to significant figures, even though the environmental facilities are elementary, but the product of thought or invention is influential to this day. This study uses a descriptive qualitative approach with library and field research methods. In contrast, data analysis uses the Milles and Huberman model, with a flow of information reduction, information arrangement, and concluding. The result of this study shows that the normative spiritualization of parents can influence simple intellectuals and progressive intellectuals. There is also a relationship between simple and advanced means, which impact originality and unoriginality.